The relationship between cognitive linguistics and neurolinguistics (Eurasian Journal of Philology Science and Education, 2022)
The article is devoted to the study of brain function, brain processes in cognition and the construction of speech activity, language acquisition and the construction of the basis of language symbolism. This science considers speech in its relationship with human cognition. Speech is presented as one of the main tools for the accumulation, systematization, processing and use of knowledge about the world. This work is devoted to the historical, scientific and methodological analysis of cognitive neuro-linguistics. The interrelation of neuro-linguistics with the philosophy of language and general linguistics is studied. Also, the article is devoted to the historical, scientific and methodological analysis of cognitive neurolinguistics, the prospects for further development of neuro-linguistics are studied. The emergence of a sound language was of great importance in the development of human consciousness. As a result of the emergence of speech, the human body has undergone anatomical changes, a speech apparatus has been developed that has the ability to articulate sound. Thanks to this, a person has acquired the ability to pronounce not only individual sounds, but also various sound phrases, words with appropriate meaning. Speech is the main sign of human consciousness. It is necessary to look for the emergence and gradual formation of speech and consciousness not only in biological conditions, but, above all, in social, historical factors. The article considers consciousness and language as a result of the historical development of human society, their activities, the ability to create and use means of labor.